ANALISIS ATRIBUT BRAND ASSOCIATION (ASOSIASI MEREK) TELEPON SELULER NOKIA (STUDI KASUS PADA MAHASISWA FAKULTAS EKONOMI UNIVERSITAS BRAWIJAYA) - Rahardjo, Toto; Farida, Siti (Jurnal Widya Manajemen & Akuntansi, 2006)
Brand association is one of brand equity dimensions. It communicates the differences and advantages of a product. Brand image, in other words, is a collection of brand association of a product. However, brand identity is a value of personality a company percepts to form its identity. This research aims at finding out which features of brand association which have great influences in Nokia users’ mind nowadays that, later on, can give some input for Nokia company whether arrange of brand association (brand image) has in line with brand identity which Nokia has. The subjects of this research are FEUB Students who use Nokia cellular phones. The method of data analysis is used Cochran Test (K Related Sample). The results of Cochran test applied in this research show that there are ten items of Nokia brand association which form the brand image; They are : cell-phones with innovative and the most complete features, variation design, a wide range of variant selections, sophisticated technology, entertaining, human technology, made by a company which is innovative, consumer oriented, and highly-selling cell-phones. These phenomenon means that there is a positive gaps and advantageous for Nokia. The company should keep the pace to defend the value it has owned. As a result the consumers will stay loyal with the brand and keep using Nokia cell-phones.